Theory and application of quasi-elastic equations in terrain-folowing coordinates based on the full pressure field - Rautenbach, C.J. de W. (Cornelis Johannes de Wet) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2006.